Comparative transcriptional profiling of human Merkel cells and Merkel cell carcinoma. Issue 12 (11th November 2014) - Mouchet, Nicolas; Coquart, Nolwenn; Lebonvallet, Nicolas; Le Gall‐Ianotto, Christelle; Mogha, Ariane; Fautrel, Alain; Boulais, Nicholas; Dréno, Brigitte; Martin, Ludovic; Hu, Weiguo; Galibert, Marie‐Dominique; Misery, Laurent
Abstract Merkel cell carcinoma is believed to be derived from Merkel cells after infection by Merkel cell polyomavirus (MCPyV) and other poorly understood events. Transcriptional profiling using cDNA microarrays was performed on cells from MCPy‐negative and MCPy‐positive Merkel cell carcinomas and isolated normal Merkel cells. This microarray revealed numerous significantly upregulated genes and some downregulated genes. The extensive list of genes that were identified in these experiments provides a large body of potentially valuable information of Merkel cell carcinoma carcinogenesis and could represent a source of potential targets for cancer therapy.